Description of a new water mite species of the genus Thyopsis (Protz, 1899) (Acari, Hydrachnidia: Hydryphantidae) from Kazakhstan - Tuzovskij, Petr V. (Zootaxa, 2021)
The world fauna of the genus Thyopsis Piersig, 1899 currently includes the following species: Th. amarginata Habeeb, 1963, Th. cancellata (Protz, 1896), Th. cancellatomima Bader, 1983, Th. majorella Habeeb, 1975, Th. oezkani Bader, 1983 and Th. rothae Oezkan, 1982 (Bader 1983). However, the taxonomic status of Th. cancellatomima remains not clear, Gerecke & Schwoerbel (1992) regarded this species as a junior synonym of Th. cancellata.